Properties of charged particle motion equations in crossed fields and Larmor’s theorem - Yeliseyev, Yu.N. (Вопросы атомной науки и техники, 2018)
Motion equations of charged particle placed in crossed fields observed in the laboratory frame of reference and in rotating one are compared. It is shown that the motion equation in fields (E, H) in a plane transverse to the magnetic field in a rotating frame has the same form as the motion equation in fields of another sstrength (E', H') in the laboratory frame. The invariant of motion equation under rotation transformation is found. A problem that is more general than the Larmor’s one is formulated and studied. There are found out the rotation frequency and the condition under which the particle motion equation in the fields (E₁, H₁) in the laboratory frame coincides with the motion equation in the fields (E₂, H₂) in the rotating frame.